Integrated tree canopy expansion and cool roofs can optimize air temperature and heat exposure reductions in Boston - Ian A. Smith; Dan Li; David K. Fork; Gregory A. Wellenius; Lucy R. Hutyra (Communications Earth & Environment)
Abstract Tree canopy expansion and albedo management represent pathways to reduce urban heat. Here we develop a statistical model to downscale coarse resolution estimates of air temperature and estimate marginal impacts of tree canopy and cool roof solutions across southern New England during 2021–2022. We quantify how tree canopy and cool roof solutions can be integrated to maximize heat exposure reduction, given feasibility and cost constraints. Afternoon estimates of air temperature cooling impacts from albedo and tree canopy cover fraction are −0.61 °C and −0.07 °C per increase of 0.1, respectively. Temperature reductions associated with tree canopy expansion are 35% higher than cool roofs, however, cool roofs on average provide higher heat exposure reductions due to implementation opportunities within dense, vulnerable regions of the city. Our Boston optimization identifies nearly twice as much area for cool roof implementation than tree canopy expansion. Cooling potential, implementation feasibility, and cost are critical considerations for identifying locally actionable, integrated climate solutions.